Orbitrap mass analyser for in situ characterisation of planetary environments: Performance evaluation of a laboratory prototype. (15th October 2016) - Briois, Christelle; Thissen, Roland; Thirkell, Laurent; Aradj, Kenzi; Bouabdellah, Abdel; Boukrara, Amirouche; Carrasco, Nathalie; Chalumeau, Gilles; Chapelon, Olivier; Colin, Fabrice; Coll, Patrice; Cottin, Hervé; et al.
Abstract: For decades of space exploration, mass spectrometry has proven to be a reliable instrumentation for the characterisation of the nature and energy of ionic and neutral, atomic and molecular species in the interplanetary medium and upper planetary atmospheres. It has been used as well to analyse the chemical composition of planetary and small bodies environments. The chemical complexity of these environments calls for the need to develop a new generation of mass spectrometers with significantly increased mass resolving power. The recently developed Orbitrap TM mass analyser at ultra-high resolution shows promising adaptability to space instrumentation, offering improved performances for in situ measurements. In this article, we report on our project named "Cosmorbitrap" aiming at demonstrating the adaptability of the Orbitrap technology for in situ space exploration. We present the prototype that was developed in the laboratory for demonstration of both technical feasibility and analytical capabilities. A set of samples containing elements with masses ranging from 9 to 208 u has been used to evaluate the performance of the analyser, in terms of mass resolving power (reaching 474, 000 at m / z 9) and ability to discriminate between isobaric interferences, accuracy of mass measurement (below 15 ppm) and determination of relative isotopic abundances (below 5%) of various samples. We observe a good agreement between the results obtained with the prototype and those of a commercial instrument. As the background pressure is a key parameter for in situ exploration of atmosphere planetary bodies, we study the effect of background gas on the performances of the Cosmorbitrap prototype, showing an upper limit for N2 in our set-up at 10 −8 mbar. The results demonstrate the strong potential to adapt this technology to space exploration. Highlights: Mass spectrometry is a reliable analytical tool for in situ space exploration. The development of mass spectrometers with high resolving power is needed. The Orbitrap mass analyser shows promising adaptability to space instrumentation. A Laser Ablation Cosmorbitrap prototype is described. Resolution, accuracy, isotopic determination, and pressure effects are presented.